Pressure events surrounding oesophageal acid reflux episodes and acid clearance in ambulant healthy volunteers. Issue 4 (April 1993) - Barham, C P; Gotley, D C; Miller, R; Mills, A; Alderson, D
Abstract : Previous studies of the mechanisms that precipitate acid reflux episodes and acid clearance have used unphysiological, short term hospital based data. A new 24 hour pH and motility recording system combined with computerised data analysis have been used to study naturally occurring acid reflux episodes in healthy ambulant volunteers. A variety of events that produced recognisable transdiaphragmatic pressure patterns were associated with acid reflux episodes (particularly belching). Peristaltic waves were the predominant contractions leading to oesophageal acid clearance and were the commonest contraction type during reflux episodes. Peristaltic wave parameters (amplitude, velocity, frequency, and percentage proportion) varied during different periods of the 24 hour recording. This study has produced new information about 24 hour oesophageal function and naturally occurring acid reflux which will provide a basis for comparison with patients with gastro-oesophageal reflux disease.